THE ISLAMIC WORK ETHICS BASED HUMAN RESOURCES PERFORMANCE IMPROVEMENT OF CIVIL SERVANTS IN SEMARANG REGENCY - Roy Ardani Muhammad; Moch Zulfa (UNISSULA, 2017)
The primary purpose of this research is to investigate and examine the effect of affective commitment and learning orientation on human resources performance through Islamic work ethic, and to propose an empirical model to investigate such correlations. A total of 164 respondents at the Civil Servants of Semarang Regency completed questionnaires on affective commitment, learning orientation, Islamic work ethic, and human resources performance. Results from structural equation modeling based AMOS 18.0 confirmed that affective commitment and learning orientation were positively related to Islamic work ethic and human resources performance; whereas Islamic work ethic was not related to human resources performance.Keywords: Affective commitment, Learning orientation, Islamic work ethic, Human resources performance